LED packaging adhesive material and preparation method thereof
By using specific types and amounts of titanium-containing zirconium vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil synthesized, the shortcomings of existing materials in high hardness, high refractive index and high light transmittance are solved, and the material performance improvement in high-power LED lighting technology has been achieved.
Patent Information
- Application Number
- CN202411923406.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
Existing LED packaging materials have shortcomings in high hardness, high refractive index and high light transmittance, especially in high-power LED lighting technology, which requires more stringent material performance.
An LED encapsulation material synthesized with specific types and amounts of titanium-containing zirconium vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil is prepared by polymerization to obtain a three-dimensional mesh structure with high crosslinking density and uniform distribution.
It realizes the high hardness, refractive index and light transmittance of LED packaging materials, and meets the strict requirements of high-power LED lighting technology for material performance.
Smart Images

Figure BDA0005208613370000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of LED technology, and more specifically, to an LED packaging adhesive material and a preparation method thereof. Background Art
[0002] Light-emitting diode (LED) is a solid light source that converts electrical energy into light energy. Packaging materials are an indispensable part of LED lighting. They protect LED chips from the influence of ambient temperature, humidity, radiation and mechanical stress. At the same time, the tolerance, transmittance and refractive index of the packaging materials themselves directly affect the luminous efficiency, brightness and service life of LEDs. In the high-power LED packaging with growing demand, the proportion of packaging materials based on silicone increases. Silicone materials have excellent thermal stability and ultraviolet radiation stability, as well as the flexibility of organic materials. At the same time, silicone packaging materials also have high transparency, resistance to cold and hot cycles and hydrophobicity. However, with the rapid development of the LED industry, especially the development of high-power LED lighting technology, the performance, stability and reliability of LED packaging materials are more stringent. In particular, among LED silicone packaging materials, high hardness, high refractive index and high transmittance LED packaging silicone materials are still dominated by imported glue. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies of the prior art and to provide an LED packaging adhesive material with high hardness, high refractive index and high light transmittance and a preparation method thereof.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides an LED encapsulation adhesive material, which comprises the following components by weight:
[0006] 100 parts of silicone oil, 1-3 parts of catalyst, 0.1-1 parts of inhibitor;
[0007] The silicone oil contains titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in a weight ratio of 1:(5-12):(2-10);
[0008] The preparation method of the titanium zirconium-containing vinyl silicone oil is as follows: phenyl siloxane, vinyl siloxane, titanate, and zirconate in a weight ratio of 0.8:(0.15-0.45):(0.05-0.3):(0.01-0.05) are polymerized to obtain the titanium zirconium-containing vinyl silicone oil;
[0009] The preparation method of the hydrogen-containing silicone oil is as follows: phenyl siloxane, titanate, zirconate, and hydrogen-containing silane coupling agent in a weight ratio of 1:(0.05-0.3):(0.01-0.05):(0.2-0.6) are polymerized to obtain the hydrogen-containing silicone oil;
[0010] The preparation method of the vinyl silicone oil is as follows: phenyl siloxane and vinyl siloxane in a weight ratio of 0.8:(0.15-0.45) are polymerized to obtain the vinyl silicone oil.
[0011] The LED packaging adhesive material synthesized by the present invention is selected from titanium zirconium vinyl silicone oil, hydrogen silicone oil and vinyl silicone oil of specific types and amounts, and the phenyl, titanium element, zirconium element and alkyl group are evenly distributed in the LED packaging adhesive material, and the three-dimensional network structure formed by the LED packaging adhesive material is compact and stable, and has a high cross-linking density, which is conducive to improving the hardness of the LED packaging adhesive material. Moreover, the LED packaging adhesive material of the present invention can also have a high refractive index and a high light transmittance.
[0012] Preferably, the weight ratio of the titanium zirconium-containing vinyl silicone oil, the hydrogen-containing silicone oil and the vinyl silicone oil is 1:(8-10):(5-8).
[0013] More preferably, the weight ratio of the titanium zirconium-containing vinyl silicone oil, the hydrogen-containing silicone oil and the vinyl silicone oil is 1:(8-10):(5.5-8).
[0014] Preferably, in the preparation method of the titanium-zirconium-containing vinyl silicone oil, the weight ratio of the phenylsiloxane, vinylsiloxane, titanate and zirconate is 0.8:0.2:(0.05-0.3):(0.01-0.05).
[0015] Preferably, in the preparation method of the vinyl silicone oil, the weight ratio of the phenyl siloxane to the vinyl siloxane is 0.8:(0.2-0.45), specifically 0.8:0.2.
[0016] The catalysts and inhibitors commonly used in the art can be used in the present invention.
[0017] Preferably, the catalyst is at least one of chloroplatinic acid, platinum tetrachloride, dichlorobis(triphenylphosphine-P-)platinum, platinum(0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, bis(triphenylphosphite)dichloroplatinum, and dichloro(dicyclopentadiene)platinum.
[0018] Preferably, the inhibitor is at least one of acetylenic compounds, maleic acid and its derivatives, fumaric acid and its derivatives.
[0019] More preferably, the acetylene compound is at least one of 1-ethynylcyclohexanol, 1-ethynyl-1-cyclopentanol, 3-methyl-1-dodecyn-3-ol, 3-phenyl-1-butyn-3-ol, and 3-methylbutynol-3.
[0020] More preferably, the maleic acid and its derivatives are at least one of maleic acid, diethyl maleate, dihexyl maleate and diallyl maleate.
[0021] More preferably, the fumaric acid and its derivatives are at least one of fumaric acid and methyl fumarate.
[0022] Preferably, in the preparation method of the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil and / or vinyl silicone oil, the phenylsiloxane is at least one of diphenyl silicone oil (CAS No.: 68083-14-7), diphenyldimethoxysilane (CAS No.: 6843-66-9), phenyltrimethoxysilane (CAS No.: 2996-92-1), and trimethoxy (p-tolyl) silane (CAS No.: 17873-01-7).
[0023] Preferably, in the preparation method of the titanium zirconium-containing vinyl silicone oil and / or vinyl silicone oil, the vinyl siloxane is at least one of dimethylvinylmethoxysilane (CAS No.: 16546-47-7) and tetramethyldivinyldisiloxane (CAS No.: 2627-95-4).
[0024] Preferably, in the preparation method of the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil, the titanate is at least one of tetrabutyl titanate (CAS No.: 5593-70-4), tetra-tert-butyl titanate (CAS No.: 3087-39-6), and tetraisopropyl titanate (CAS No.: 546-68-9).
[0025] Preferably, in the preparation method of the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil, the zirconate is at least one of zirconium n-propoxide (CAS No.: 23519-77-9), zirconium isopropoxide (CAS No.: 2171-98-4), zirconium tert-butoxide (CAS No.: 2081-12-1), and tetrabutyl zirconate (CAS No.: 1071-76-7).
[0026] Preferably, in the preparation method of the hydrogen-containing silicone oil, the hydrogen-containing silane coupling agent is at least one of trimethoxysilane (CAS No.: 2487-90-3), tetramethyldisiloxane (CAS No.: 3277-26-7), and pentamethyldisiloxane (CAS No.: 1438-82-0).
[0027] Preferably, the preparation method of the titanium zirconium-containing vinyl silicone oil is specifically as follows:
[0028] (1) mixing phenyl siloxane, vinyl siloxane, an organic solvent, an acid catalyst and water to obtain a mixture X;
[0029] (2) mixing titanate, zirconate, an organic solvent, an acid catalyst and mixture X to obtain mixture Y;
[0030] (3) Adjust the pH of the mixture Y to 6.5-7.5, and heat to react to obtain titanium-zirconium-containing vinyl silicone oil.
[0031] More preferably, in step (1) and / or (2), the organic solvent is at least one of ethanol, isopropanol and n-butanol.
[0032] More preferably, in step (1), the mixing temperature is 20-50°C and the mixing time is 4-16 hours, specifically, the mixing temperature is 30°C and the mixing time is 12 hours.
[0033] More preferably, in step (1), the pH condition of the mixing is pH=2-5.
[0034] More preferably, in step (1), the acid catalyst is at least one of hydrochloric acid, sulfuric acid, acetic acid and p-toluenesulfonic acid; the mass of the acid catalyst is 1-5% of the total mass of phenylsiloxane and vinylsiloxane.
[0035] More preferably, in step (2), the mixing temperature is 20-65°C and the mixing time is 4-8h, specifically, the mixing temperature is 30°C and the mixing time is 6h.
[0036] More preferably, in step (2), the acid catalyst is at least one of hydrochloric acid, sulfuric acid, acetic acid and p-toluenesulfonic acid; the mass of the acid catalyst is 1-5% of the total mass of the titanate and the zirconate.
[0037] In step (3) of the present invention, the pH regulator is a pH regulator commonly used in the art, such as triethylamine.
[0038] More preferably, in step (3), the heating reaction temperature is 100-160° C. and the time is 2-8 h.
[0039] More preferably, in step (3), after the heating reaction, reduced pressure distillation is also included; the purpose of the reduced pressure distillation is to remove the solvent in the system.
[0040] Preferably, the preparation method of the hydrogen-containing silicone oil is specifically as follows:
[0041] A. Mix organic solvent, phenyl siloxane, titanate, zirconate and hydrogen-containing silane coupling agent, heat and react to obtain hydrogen-containing silicone oil.
[0042] More preferably, in step A, the mixing further comprises a catalyst.
[0043] More preferably, the mass of the catalyst is 1-5% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent; catalysts commonly used in the art can be used in the present invention, such as at least one of hydrochloric acid, sulfuric acid, acetic acid and p-toluenesulfonic acid.
[0044] More preferably, in step A, the heating reaction is carried out at 60-120° C. for 2-6 hours.
[0045] More preferably, in step A, after the heating reaction, reduced pressure distillation is further included; the purpose of the reduced pressure distillation is to remove the solvent in the system.
[0046] More preferably, in step A, the heating reaction is carried out under the protection of an inert gas; any inert gas commonly used in the art can be used in the present invention, such as nitrogen.
[0047] More preferably, in step A, the mass of the organic solvent is 30-60% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent; organic solvents commonly used in the art can be used in the present invention, such as toluene.
[0048] Preferably, the preparation method of the vinyl silicone oil is specifically as follows:
[0049] B. Mix organic solvent, phenyl siloxane and vinyl siloxane, heat and react to obtain vinyl silicone oil.
[0050] More preferably, in step B, the mixing further comprises a catalyst.
[0051] More preferably, the mass of the catalyst is 1-5% of the total mass of phenylsiloxane and vinylsiloxane; catalysts commonly used in the art can be used in the present invention, such as at least one of hydrochloric acid, sulfuric acid, acetic acid and p-toluenesulfonic acid.
[0052] More preferably, in step B, the heating reaction is performed at 60-120° C. for 2-6 h.
[0053] More preferably, in step B, after the heating reaction, reduced pressure distillation is further included; the purpose of the reduced pressure distillation is to remove the solvent in the system.
[0054] More preferably, in step B, the heating reaction is carried out under the protection of an inert gas; any inert gas commonly used in the art can be used in the present invention, such as nitrogen.
[0055] More preferably, in step B, the mass of the organic solvent is 30-60% of the total mass of the phenylsiloxane and the vinylsiloxane; organic solvents commonly used in the art can be used in the present invention, such as toluene.
[0056] In a second aspect, the present invention provides a method for preparing an LED encapsulation adhesive material, comprising the following steps:
[0057] The components are mixed to obtain LED packaging adhesive material.
[0058] Preferably, after mixing the components, ultrasonic degassing is also included.
[0059] Preferably, the ultrasonication time is 15-30 min.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] The LED packaging adhesive material synthesized by the present invention is selected from titanium zirconium vinyl silicone oil, hydrogen silicone oil and vinyl silicone oil of specific types and amounts, and the phenyl, titanium element, zirconium element and alkyl group are evenly distributed in the LED packaging adhesive material, and the three-dimensional network structure formed by the LED packaging adhesive material is compact and stable, and has a high cross-linking density, which is conducive to improving the hardness of the LED packaging adhesive material. Moreover, the LED packaging adhesive material of the present invention can also have a high refractive index and a high light transmittance. DETAILED DESCRIPTION
[0062] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0063] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or according to conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0064] Example 1
[0065] This embodiment provides an LED encapsulation adhesive material, which includes the following components by weight:
[0066] 100 parts of silicone oil, 2 parts of catalyst (chloroplatinic acid), 0.5 parts of inhibitor (1-ethynylcyclohexanol);
[0067] The silicone oil contains titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in a weight ratio of 1:8:5.5;
[0068] in:
[0069] The preparation method of the titanium zirconium-containing vinyl silicone oil comprises the following steps:
[0070] (1) mixing phenylsiloxane (diphenyldimethoxysilane), vinylsiloxane (dimethylvinylmethoxysilane), an organic solvent (isopropanol), an acid catalyst (hydrochloric acid) and water at 30° C. and pH=3 (pH adjusted with hydrochloric acid) for 12 h to obtain a mixture X;
[0071] (2) mixing titanate (tetrabutyl titanate), zirconate (zirconium n-propoxide), organic solvent (isopropanol), acid catalyst (hydrochloric acid) and mixture X at 30° C. for 6 hours to obtain mixture Y;
[0072] (3) adjusting the pH of the mixture Y to 7 with triethylamine, heating the mixture at 100° C. for 6 h, and removing the solvent by distillation under reduced pressure to obtain titanium-zirconium-containing vinyl silicone oil;
[0073] In step (1), the volume ratio of the organic solvent (isopropanol) to water is 1:0.8, the mass of the water is 30% of the total mass of phenylsiloxane (diphenyldimethoxysilane) and vinylsiloxane (dimethylvinylmethoxysilane), and the mass of the acid catalyst (hydrochloric acid) is 2% of the total mass of phenylsiloxane and vinylsiloxane;
[0074] In step (2), the mass of the organic solvent (isopropanol) is 40% of the total mass of the titanate (tetrabutyl titanate) and the zirconate (zirconium n-propoxide), and the mass of the acid catalyst (hydrochloric acid) is 2% of the total mass of the phenylsiloxane and the vinylsiloxane;
[0075] The weight ratio of the phenylsiloxane, vinylsiloxane, titanate and zirconate is 0.8:0.2:0.3:0.05;
[0076] The preparation method of the hydrogen-containing silicone oil comprises the following steps:
[0077] A. Mix the catalyst (sulfuric acid), organic solvent (toluene), phenylsiloxane (diphenyldimethoxysilane), titanate (tetrabutyl titanate), zirconate (zirconium n-propoxide) and hydrogen-containing silane coupling agent (tetramethyldisiloxane), heat at 90°C for 4 hours under the protection of inert gas nitrogen, and remove the solvent by distillation under reduced pressure to obtain hydrogen-containing silicone oil;
[0078] In step A, the mass of the catalyst (sulfuric acid) is 2% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent, and the mass of the organic solvent is 50% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent;
[0079] The weight ratio of the phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent is 1:0.3:0.05:0.6;
[0080] The preparation method of the vinyl silicone oil comprises the following steps:
[0081] B. Mix the catalyst (sulfuric acid), organic solvent (toluene), phenylsiloxane (diphenyldimethoxysilane) and vinylsiloxane (dimethylvinylmethoxysilane), heat at 80°C for 5 hours under the protection of inert gas nitrogen, and remove the solvent by distillation under reduced pressure to obtain vinyl silicone oil;
[0082] In step B, the mass of the catalyst is 3% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent, and the mass of the organic solvent is 50% of the total mass of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent;
[0083] The weight ratio of the phenyl siloxane to the vinyl siloxane is 0.8:0.2.
[0084] The method for preparing the above-mentioned LED packaging adhesive material comprises the following steps:
[0085] The components were mixed and subjected to ultrasonic degassing for 20 minutes to obtain the LED encapsulation adhesive material.
[0086] Examples 2-7 and Comparative Examples 1-5
[0087] Examples 2-7 and Comparative Examples 1-5 provide different LED encapsulation adhesive materials, which differ from Example 1 in that the weight ratios of titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil are different, and the rest are consistent with Example 1, as shown in the following table:
[0088] Table 1 Weight ratio of titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in Examples 1-7 and Comparative Examples 1-5
[0089] Weight ratio of titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil Example 1 1:8:5.5 Example 2 1:10:5.5 Example 3 1:5:5.5 Example 4 1:12:5.5 Example 5 1:8:8 Example 6 1:8:2 Example 7 1:8:10 Comparative Example 1 1:15:5.5 Comparative Example 2 1:8:15 Comparative Example 3 0:8:5.5 Comparative Example 4 1:0:5.5 Comparative Example 5 1:8:0
[0090] Example 8 and Comparative Examples 6-7
[0091] Example 8 and Comparative Examples 6-7 provide different LED encapsulation adhesive materials, which differ from Example 1 in that in the preparation method of titanium zirconium-containing vinyl silicone oil, the weight ratios of phenylsiloxane (diphenyldimethoxysilane), vinylsiloxane (dimethylvinylmethoxysilane), titanate (tetrabutyl titanate), and zirconate (zirconium n-propoxide) are different, that is, the types of titanium zirconium-containing vinyl silicone oil are different, and the rest are consistent with Example 1, as shown in the following table:
[0092] Table 2 Weight ratio of phenylsiloxane, vinylsiloxane, titanate, and zirconate in the preparation method of titanium-zirconium vinyl silicone oil in Examples 1, 8 and Comparative Examples 6-7
[0093] Weight ratio of phenyl siloxane, vinyl siloxane, titanate, zirconate Example 1 0.8:0.2:0.3:0.05 Example 8 0.8:0.2:0.05:0.01 Comparative Example 6 0.8:0.8:0.5:0.1 Comparative Example 7 0.8:0.2:0:0
[0094] Example 9 and Comparative Examples 8-10
[0095] Example 9 and Comparative Examples 8-10 provide different LED encapsulation adhesive materials, which differ from Example 1 in that in the preparation method of hydrogen-containing silicone oil, the weight ratios of phenylsiloxane (diphenyldimethoxysilane), titanate (tetrabutyl titanate), zirconate (zirconium n-propoxide), and hydrogen-containing silane coupling agent (tetramethyldisiloxane) are different, that is, the types of hydrogen-containing silicone oil are different, and the rest are consistent with Example 1, as shown in the following table:
[0096] Table 3 Weight ratio of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent in the preparation method of hydrogen-containing silicone oil in Examples 1, 9 and Comparative Examples 8-10
[0097] Weight ratio of phenylsiloxane, titanate, zirconate and hydrogen-containing silane coupling agent Example 1 1:0.3:0.05:0.6 Example 9 1:0.05:0.01:0.2 Comparative Example 8 1:0.5:0.1:0.8 Comparative Example 9 1:0.3:0.05:0 Comparative Example 10 1:0:0:0.6
[0098] Example 10 and Comparative Examples 11-12
[0099] Example 10 and Comparative Examples 11-12 provide different LED encapsulation adhesive materials, which differ from Example 1 in that in the preparation method of vinyl silicone oil, the weight ratio of phenylsiloxane (diphenyldimethoxysilane) and vinylsiloxane (dimethylvinylmethoxysilane) is different, that is, the types of vinyl silicone oil are different, and the rest are consistent with Example 1, as shown in the following table:
[0100] Table 4 Weight ratio of phenyl siloxane to vinyl siloxane in the preparation method of vinyl silicone oil in Examples 1, 10 and Comparative Examples 11-12
[0101] Weight ratio of phenyl siloxane and vinyl siloxane Example 1 0.8:0.2 Example 10 0.8:0.45 Comparative Example 11 0.8:0.6 Comparative Example 12 0.8:0.05
[0102] Embodiment 11
[0103] This embodiment provides an LED encapsulation adhesive material, which includes the following components by weight:
[0104] 100 parts of silicone oil, 1 part of catalyst (platinum tetrachloride), 0.1 part of inhibitor (diethyl maleate);
[0105] The silicone oil contains titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in a weight ratio of 1:8:5.5;
[0106] The preparation method of the titanium zirconium-containing vinyl silicone oil is consistent with that in Example 1;
[0107] The preparation method of the hydrogen-containing silicone oil is consistent with that in Example 1;
[0108] The preparation method of the vinyl silicone oil is consistent with that in Example 1;
[0109] The preparation method of the above LED packaging adhesive material is consistent with that of Example 1.
[0110] Example 12
[0111] This embodiment provides an LED encapsulation adhesive material, which includes the following components by weight:
[0112] 100 parts of silicone oil, 3 parts of catalyst [bis(triphenyl phosphite)platinum dichloride], 1 part of inhibitor (3-methylbutynol-3);
[0113] The silicone oil contains titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in a weight ratio of 1:8:5.5;
[0114] The preparation method of the titanium zirconium-containing vinyl silicone oil is consistent with that in Example 1;
[0115] The preparation method of the hydrogen-containing silicone oil is consistent with that in Example 1;
[0116] The preparation method of the vinyl silicone oil is consistent with that in Example 1;
[0117] The preparation method of the above LED packaging adhesive material is consistent with that of Example 1.
[0118] Performance Testing
[0119] The performance test of the LED packaging adhesive material of each embodiment and comparative example is carried out, and the specific test method is as follows:
[0120] (1) Transmittance, Shore A hardness, refractive index and yellowing resistance test
[0121] The LED encapsulation adhesive material was placed in a circular mold, first cured at 80°C for 1h, then cured at 150°C for 3h, to make a 4mm test block, and then the transmittance, Shore A hardness and refractive index tests were performed respectively;
[0122] Light transmittance: Make the LED encapsulation adhesive material into a disc with a diameter of 30mm and a height of 4mm. Use a UV-visible light photometer to test the light transmittance of the LED encapsulation adhesive material disc at a wavelength of 400nm. The light transmittance ≥90% is the qualified standard.
[0123] Shore A hardness: The LED encapsulation adhesive material is made into a disc with a diameter of 30mm and a height of 4mm, and the hardness is tested using a Shore A hardness tester; Shore A hardness ≥ 75 is the qualified standard;
[0124] Refractive index: tested using an Abbe refractometer; a refractive index ≥1.52 is considered acceptable;
[0125] Yellowing resistance: Use ultraviolet lamp test, UV-A light source, place on the blackboard temperature 40℃ for 48h, and conduct yellowing resistance test. Use colorimeter to test the Lab value of the test sample before and after the test, and calculate the change of b value. The greater the change of b value, the greater the b value is, the record is bad, and the bad rate is calculated. The higher the bad rate is, the worse the yellowing resistance of the tested LED packaging glue material is.
[0126] Among them, the greater the Shore A hardness of the LED encapsulation glue material, the greater the hardness of the LED encapsulation glue material;
[0127] (2) Red ink, sulfur resistance and high temperature and high humidity aging test
[0128] First, cure at 80℃ for 1h, then cure at 150℃ for 3h, make the LED encapsulation glue material into glue-dispensing lamp beads, and then conduct red ink, sulfur resistance, yellowing resistance and high temperature and high humidity aging tests respectively;
[0129] Red ink test: Soak the dispensing lamp beads in red ink, heat at 120℃ for 2h, take them out, and use a magnifying glass to observe whether the red ink has penetrated into the glue of the dispensing lamp beads, and test whether the dispensing lamp beads can work normally, and calculate the defective rate; the higher the defective rate, the worse the bonding performance of the tested LED packaging glue material.
[0130] Sulfur resistance test: Use double-sided tape to stick the glued lamp beads on the filter paper, put 0.5g of dry sublimated sulfur powder in a 1000ml beaker, place the filter paper with the glued lamp beads on the top of the beaker mouth, and the lamp beads face the inside of the beaker, use a rubber band to tie the filter paper with the glued lamp beads to the beaker mouth, put it in an 80℃ oven for 5h, take it out, check whether the packaging part of the glued lamp beads turns black, and calculate the defective rate; the higher the defective rate, the less sufficient the curing degree of the tested LED packaging glue material.
[0131] High temperature and high humidity aging test: Place the dispensed lamp beads in an environment of 85°C and 85% relative humidity (RH) for 168 hours. After the test is completed, check whether the appearance of the dispensed lamp beads is abnormal and calculate the defective rate; the higher the defective rate, the worse the aging resistance of the tested LED packaging glue material.
[0132] Table 5 Performance test results of LED packaging adhesive materials in various embodiments and comparative examples
[0133]
[0134] As can be seen from Table 5, the LED packaging adhesive material synthesized by the present invention by selecting specific types and amounts of titanium-zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil has a high uniform distribution of phenyl, titanium element, zirconium element and alkyl inside, and the three-dimensional network structure formed is compact and stable, with a high cross-linking density, which is conducive to improving the high hardness of the LED packaging adhesive material. In addition, the LED packaging adhesive material of the present invention can also have a high refractive index and high light transmittance.
[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An LED packaging adhesive material, characterized in that: Calculated by weight, it includes the following components: 100 parts of silicone oil, 1-3 parts of catalyst, 0.1-1 parts of inhibitor; The silicone oil contains titanium zirconium-containing vinyl silicone oil, hydrogen-containing silicone oil and vinyl silicone oil in a weight ratio of 1:(5-12):(2-10); The preparation method of the titanium zirconium-containing vinyl silicone oil is as follows: phenyl siloxane, vinyl siloxane, titanate, and zirconate in a weight ratio of 0.8:(0.15-0.45):(0.05-0.3):(0.01-0.05) are polymerized to obtain the titanium zirconium-containing vinyl silicone oil; The preparation method of the hydrogen-containing silicone oil is as follows: phenyl siloxane, titanate, zirconate, and hydrogen-containing silane coupling agent in a weight ratio of 1:(0.05-0.3):(0.01-0.05):(0.2-0.6) are polymerized to obtain the hydrogen-containing silicone oil; The preparation method of the vinyl silicone oil is as follows: phenyl siloxane and vinyl siloxane in a weight ratio of 0.8:(0.15-0.45) are polymerized to obtain the vinyl silicone oil.
2. The LED packaging adhesive material according to claim 1, characterized in that: The weight ratio of the titanium zirconium-containing vinyl silicone oil, the hydrogen-containing silicone oil and the vinyl silicone oil is 1:(8-10):(5-8).
3. The LED packaging adhesive material according to claim 1, characterized in that: In the preparation method of the titanium-zirconium-containing vinyl silicone oil, the weight ratio of the phenylsiloxane, vinylsiloxane, titanate and zirconate is 0.8:0.2:(0.05-0.3):(0.01-0.05).
4. The LED packaging adhesive material according to claim 1, characterized in that: In the preparation method of the vinyl silicone oil, the weight ratio of the phenyl siloxane to the vinyl siloxane is 0.8:(0.2-0.45).
5. The LED packaging adhesive material according to claim 1, characterized in that: Include at least one of the following: a. The catalyst is at least one of chloroplatinic acid, platinum tetrachloride, dichlorobis(triphenylphosphine-P-)platinum, platinum(0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, bis(triphenylphosphite)dichloroplatinum, and dichloro(dicyclopentadiene)platinum; b. The inhibitor is at least one of acetylenic compounds, maleic acid and its derivatives, fumaric acid and its derivatives.
6. The LED packaging adhesive material according to claim 1, characterized in that: Include at least one of the following: a. In the method for preparing the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil and / or vinyl silicone oil, the phenylsiloxane is at least one of diphenyl silicone oil, diphenyldimethoxysilane, phenyltrimethoxysilane and trimethoxy(p-tolyl)silane; b. In the method for preparing the titanium zirconium-containing vinyl silicone oil and / or vinyl silicone oil, the vinyl siloxane is at least one of dimethylvinylmethoxysilane and tetramethyldivinyldisiloxane; c. In the method for preparing the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil, the titanate is at least one of tetrabutyl titanate, tetra-tert-butyl titanate, and tetraisopropyl titanate; d. In the method for preparing the titanium zirconium-containing vinyl silicone oil and / or hydrogen-containing silicone oil, the zirconate is at least one of zirconium n-propoxide, zirconium isopropoxide, zirconium tert-butoxide, and tetrabutyl zirconate; e. In the preparation method of the hydrogen-containing silicone oil, the hydrogen-containing silane coupling agent is at least one of trimethoxysilane, tetramethyldisiloxane, and pentamethyldisiloxane.
7. The LED packaging adhesive material according to claim 1, characterized in that: The preparation method of the titanium zirconium-containing vinyl silicone oil is specifically as follows: (1) mixing phenyl siloxane, vinyl siloxane, an organic solvent, an acid catalyst and water to obtain a mixture X; (2) mixing titanate, zirconate, an organic solvent, an acid catalyst and mixture X to obtain mixture Y; (3) Adjust the pH of the mixture Y to 6.5-7.5, and heat the mixture for reaction to obtain titanium-zirconium-containing vinyl silicone oil.
8. The LED packaging adhesive material according to claim 7, characterized in that: Include at least one of the following: a. In step (1), the mixing temperature is 20-50°C; b. In step (2), the mixing temperature is 20-65°C; c. In step (3), the temperature of the heating reaction is 100-160°C.
9. The LED packaging adhesive material according to claim 1, characterized in that: The preparation method of the hydrogen-containing silicone oil is specifically as follows: A. Mix organic solvent, phenyl siloxane, titanate, zirconate and hydrogen-containing silane coupling agent, heat and react to obtain hydrogen-containing silicone oil.
10. The LED packaging adhesive material according to claim 1, characterized in that: The preparation method of the vinyl silicone oil is specifically as follows: B. Mix organic solvent, phenyl siloxane and vinyl siloxane, and heat to react to obtain vinyl silicone oil.
Citation Information
Cited By
Preparation device of LED encapsulation adhesive film
CN224614225U